2019
DOI: 10.1177/1090198119831060
|View full text |Cite
|
Sign up to set email alerts
|

Insuring Good Health: Outcomes and Acceptability of a Participatory Health Insurance Literacy Intervention in Diverse Urban Communities

Abstract: Background. The U.S. uninsured rate has dropped significantly since the passage of the Affordable Care Act (ACA), yet insurance coverage remains lower in historically marginalized communities than in the overall population. New consumer engagement approaches that involve these populations are needed. The purpose of this study was to evaluate the effectiveness of the Insuring Good Health Intervention, a website and video series designed to improve engagement with health insurance and ACA reforms. The study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“… 32 Another study in the metropolitan Detroit area evaluated an online intervention comprised of a website and video series called ‘Insuring Good Health’, which aimed to promote engagement with health insurance. 33 The website is primarily focused on providing information on insurance enrolment. It defines common insurance terminology such as premiums, but does not mention HDHPs or discuss specific cost-conscious strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 32 Another study in the metropolitan Detroit area evaluated an online intervention comprised of a website and video series called ‘Insuring Good Health’, which aimed to promote engagement with health insurance. 33 The website is primarily focused on providing information on insurance enrolment. It defines common insurance terminology such as premiums, but does not mention HDHPs or discuss specific cost-conscious strategies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the intervention did not significantly increase health insurance literacy or confidence in navigating one’s health plan. 33 Our intervention is the first to our knowledge which provides information on multiple cost-conscious strategies for HDHP enrollees in a structured set of educational modules.…”
Section: Discussionmentioning
confidence: 99%
“…Given the complexity that exists in the American healthcare system today, there is a clear opportunity to leverage digital platforms to elevate and promote health insurance literacy. Patel et al found the use of a website and video series featuring relatable characters overcoming common challenges and meeting personal goals in health situations resulted in stronger intention to seek help with health insurance navigation in racial and ethnic minorities [9]. The federal government has already created resources aimed at educating consumers about health insurance, such as the CMS Coverage to Care website [10].…”
mentioning
confidence: 99%
“…Along the way, health education and promotion specialists can advance health insurance literacy by developing and delivering educational programs through academic extension programs, adult education venues, and public health outreach settings. Such programs, albeit on a limited scale, have shown promise in increasing individual-level knowledge and skills and improving the capacity to make optimal health insurance purchases ( Brown et al, 2016 ; Brown, 2018 ; Patel et al, 2019 ).…”
mentioning
confidence: 99%